Biomarker monitoring in sports doping control. (May 2012) - Pottgiesser, Torben; Schumacher, Yorck Olaf
Biomarker monitoring can be considered a new era in the effort against doping. Opposed to the old concept in doping control of direct detection of a prohibited substance in a biological sample such as urine or blood, the new paradigm allows a personalized longitudinal monitoring of biomarkers that indicate non-physiological responses independently of the used doping technique or substance, and may cause sanctioning of illicit practices. This review presents the development of biomarker monitoring in sports doping control and focuses on the implementation of the Athlete Biological Passport as the current concept of the World Anti Doping Agency for the detection of blood doping (hematological module). The scope of the article extends to the description of novel biomarkers and future concepts of application.